2018
DOI: 10.1039/c7sc04712f
|View full text |Cite
|
Sign up to set email alerts
|

Tuning protein folding in lysosomal storage diseases: the chemistry behind pharmacological chaperones

Abstract: We review pharmacological chaperones used in lysosomal storage diseases, emphasizing medicinal chemistry approaches and mechanisms of action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 84 publications
(101 reference statements)
1
55
0
Order By: Relevance
“…Agents that are at earlier developmental stages include N octylβ valienamine, a competitive inhibitor of βglucosidase, for Gaucher disease; N acetylcysteine for Pompe disease; α lobeline, 3,4,7trihydroxyisoflavone and azasugar in Krabbe disease; and N octyl4epi β valienamine and 5N,6S(N′butyliminomethylidene) 6thio1deoxygalactonojirimycin indicated in GM1 gangliosidosis 289 . The chemical structures of these pharmacological chaperones have been described recently 290,291 . Finally, an alternative strategy for stabiliz ing mutant enzymes, by binding away from the active site, is also being investigated.…”
Section: Substrate Reduction Therapies and Small-molecule Chaperonesmentioning
confidence: 99%
See 1 more Smart Citation
“…Agents that are at earlier developmental stages include N octylβ valienamine, a competitive inhibitor of βglucosidase, for Gaucher disease; N acetylcysteine for Pompe disease; α lobeline, 3,4,7trihydroxyisoflavone and azasugar in Krabbe disease; and N octyl4epi β valienamine and 5N,6S(N′butyliminomethylidene) 6thio1deoxygalactonojirimycin indicated in GM1 gangliosidosis 289 . The chemical structures of these pharmacological chaperones have been described recently 290,291 . Finally, an alternative strategy for stabiliz ing mutant enzymes, by binding away from the active site, is also being investigated.…”
Section: Substrate Reduction Therapies and Small-molecule Chaperonesmentioning
confidence: 99%
“…Further testing of NCGC607 in patients with PD and GBA mutations is awaited. Although promis ing, conflicting viewpoints still remain on the strength of such small molecule based approaches, primarily because these compounds bind to the catalytic site of enzymes, which may be a risk at high concentrations if they inhibit rather than increase activity 291,292 . More clinical trials are therefore required in order to analyse the robustness of this approach.…”
Section: Substrate Reduction Therapies and Small-molecule Chaperonesmentioning
confidence: 99%
“…Pathophysiological studies in different LSDs have suggested that in some cases, the amino acid change leads to loss of protein stability due to changes in their processing, folding, glycosylation, and pH stability, which promotes aggregation and can induce ER or Golgi apparatus retention and/or increased degradation, or defective transport to the lysosomes [37][38][39][40][41][42][43][44][45][46][47][48]. In this sense, the use of PCs as an alternative to restore the folding and trafficking of the mutated lysosomal proteins has been proposed [19,20]. It has been observed that PCs can increase the enzyme activity of the mutant proteins in a mutation-dependent manner, which may be sufficient to ameliorate most disease symptoms [49,50].…”
Section: Use Of Pharmacological Chaperones In Lsdsmentioning
confidence: 99%
“…Pharmacological chaperones have ceased to be a niche category and have entered the clinical practice for some rare diseases caused primarily by protein instability. Many reviews exist to cover this subject with different points of view (a few examples [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]). We wanted to contribute by providing the readers with a list of research papers organized per disease that covers the years from 2000 to 2018.…”
Section: Introductionmentioning
confidence: 99%